Morphology and Redescription of Endemic Baikal Planarians of the Genus Archicotylus Korotneff, 1912 - A.G. Porfiriev (Учёные записки Казанского университета: Серия Естественные науки)
This paper is a taxonomic revision of endemic Baikal planarians of the genus Archicotylus. Despite the long history of research on this group in the 20th century, the fauna of Baikal planarians remains insufficiently studied. The genus Archicotylus is a complex group that is of highest interest among all groups of Baikal tricladids. In earlier studies, small-sized tricladids without adenodactyls, which are characterized by a vague systematic position and the absence of any excessive adaptations or structural deviations from the standard scheme of the Probursalia (Tricladida) copulative organ, were ascribed to this genus. To date, the genus Archicotylus comprises the following species, all distanced from each other to a various degree: A. decoloratus, A. elongatus, A. planus, A. junca, A. rubzowi, and A. parvipunctatus. An illustrated description of all species belonging to the genus Archicotylus is provided here. We have singled out certain distinctive features that are characteristic of different species groups within the genus. Previously, we distinguished several dwarf species (Microarchicotylus stringulatus, M. elegans, and M. ochroleucus) from the genus Archicotylus and included them into the new genus Microarchicotylus of Baikal planarians. Microarchicotylus planarians have similar external features: small body size and a pair of eyes with a collar behind them. They also share a common structure of the skin-muscular sac of the pharynx and the copulative organ, which is compact and resides behind the pharynx, with its apical part directed downwards.